Follower-Leader Development: Uncovering Micro-moments of Female Student-athlete Leader Development - Zack Damon; Jon Welty Peachey; Janelle Wells; Drew Pickett; Jeff Ward (University of Kansas Libraries, 2024)
Most scholarly attention within sport management leadership research has focused on four main leadership theories: authentic, servant, transactional, and transformational. While recent research included the social construction of leadership and a call to explore more follower-centric aspects of leadership, little empirical research has focused on how leaders develop, or more succinctly - leader development. Much of the leader development literature to date has mainly focused on large interventions or outcomes, oftentimes overlooking day-to-day, micro-moments of leader development. In sport-related research there has been a paucity of research directly addressing development of women and girls as leaders. The purpose of the current study, therefore, was to determine how female intercollegiate student-athletes develop into leaders through micro-moments. This study employed a qualitative approach using interviews and observations. Participants included two National Collegiate Athletic Association (NCAA) Division III female teams. Three themes emerged from qualitative semi-structured interviews (N = 30) and observations (12 hours total) identifying the micro-moments of development: empowerment, modeling leadership, and peer-to-peer leadership. Findings explain how these micro-moments aid in the leader development process. The study enhances a theoretical understanding of intercollegiate student-athlete leader development.